Sistem Informasi Pemesanan Tiket Travel Berbasis Web pada PT. Raja Travel Rantauprapat - Santriana, Eka (Journal of Computer Science and Information System(JCoInS), 2023)
Writing this Final Project after making a plan based on information on car travel ticket sales, then all data storage would be important for the management of the company must be recorded in the relations report, so far it is still very simple categorized by using archives and ledgers, so the calculation and workmanship process is in dire need a long time, and there are certainly many errors entering data. Therefore it is certain that the system that has been running so far is inefficient and relevant. Formulation of the problem of how to design a web-based ticket booking information system at PT. Raja Travel Rantauprapat, how to make web-based ticket booking information at PT. King of Travel Rantauprapat computerized, how to get ticket booking reports quickly and better. The program used is (program name and description). These results indicate that making a web-based ticket booking information system at PT. Raja Travel Rantauprapat uses the WEB programming language, making the search process information on travel ticket booking data at PT. Raja Travel Rantauprapat, get a report on travel ticket booking data information at PT. Raja Travel Rantauprapat quickly and accurately.